2020
DOI: 10.1016/j.clon.2019.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Stereotactic Ablative Radiotherapy for Recurrent or Oligometastatic Tumours in Children and Young Adults

Abstract: Aims: Cancer remains a leading cause of death in children and adolescents in the developed world. Despite advances in oncological management, rates of primary treatment failure remain significant. Radiation of recurrent or metastatic disease improves survival in adults but there is little data to support clinical decision making in the paediatric/teenage and young adult population. Materials and methods: We present a retrospective case series of 14 patients treated with stereotactic ablative body radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Also in the literature, evidence for hypofractionated stereotactic radiotherapy in children is limited. Some studies showed the feasibility of a stereotactic technique, with varying dose and fractionation schemes [26,39,45]. Local control rates ranged from 50 to 85% at a median follow-up of 2 years, with no acute or severe late toxicities observed [26,39,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in the literature, evidence for hypofractionated stereotactic radiotherapy in children is limited. Some studies showed the feasibility of a stereotactic technique, with varying dose and fractionation schemes [26,39,45]. Local control rates ranged from 50 to 85% at a median follow-up of 2 years, with no acute or severe late toxicities observed [26,39,44].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed the feasibility of a stereotactic technique, with varying dose and fractionation schemes [26,39,45]. Local control rates ranged from 50 to 85% at a median follow-up of 2 years, with no acute or severe late toxicities observed [26,39,44]. Casey et al retrospectively evaluated the indications for a radiotherapy dose and fractionation schedule with curative intent of 49 bone metastases in RMS and ES patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We enrolled young patients because that patients receiving SBRT reported overall good quality of life in general, associated with better global health status and lower indirect costs of productivity loss [15,16], which are much more important in young rather than old patients. In children and young adults, SBRT prolonged overall survival without signi cant toxicities [17]. The maturation of SBRT contributed to decades of technical and clinical advancement, including managing cardiac and respiratory motions, de ning safe radiation dosing levels for critical organs, and setting quality assurance standards globally.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the current radiotherapy approach for oligometastatic disease is strongly focused on hypofractionation and outcomes are associated with favourable local tumour control and limited toxicity for lesions within the bone, lymph nodes and soft tissue [10][11][12][13]. In contrast, the available literature on hypofractionation in children is mainly limited to retrospective and case studies for both cranial and extra-cranial metastatic disease [14][15][16]. In these studies, dose and fractionation schedules varied widely (total dose range 20-60 Gy in 1-10 fractions, dose per fraction range 5-20 Gy).…”
mentioning
confidence: 99%